Effect of Zr Doping on Structure and Ferroelectric Properties of Nanostructured Barium Titanate - Mohamed M. Salem; Aseel M. Altarawneh; Yamen A. Alibwaini; Ryad Ghazy; Osama M. Hemeda; Di Zhou; Moustafa A. Darwish; M. Khalid Hossain; Daria I. Tishkevich; Tatiana I. Zubar; Ekaterina L. Trukhanova; Alex V. Trukhanov; et al. (Nano Select)
ABSTRACT Using soft chemistry methods, solid solutions of BaTi1‐xZrxO3 with 0 ≤ x ≤ 1 were obtained. The phase nature and features of the perovskite crystalline structure were established by x‐ray analysis and Fourier transform infrared (FTIR) spectroscopy. It was found that the average particle size increases with increasing content of zirconium cations. The average size of the crystallites, which are mostly irregular in shape and closely connected, is ∼43 nm. The d33 piezoelectric coefficient decreases while the concentration of zirconium cations increases. It is interesting to note that the residual polarization very strongly depends on the average crystallite size and, on the contrary, increases with increasing concentration of zirconium cations. The discovered behavior can be used in the design and production of electrostatic read‐only memory devices.